2021
DOI: 10.1063/9.0000166
|View full text |Cite
|
Sign up to set email alerts
|

Embedded quantum-error correction and controlled-phase gate for molecular spin qubits

Abstract: A scalable architecture for quantum computing requires logical units supporting quantum-error correction. In this respect, magnetic molecules are particularly promising, since they allow one to define logical qubits with embedded quantum-error correction by exploiting multiple energy levels of a single molecule. The single-object nature of this encoding is expected to facilitate the implementation of error correction procedures and logical operations. In this work, we make progress in this direction by showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…30 On the other, effective qudit QEC codes can be implemented exploiting the d = 2S + 1 levels of a spin S system. 49,51,52 The first approach was investigated in Ref. 30, where it was shown that an [ErCeEr] trimer is a promising molecule to encode a logical qubit protected against dephasing by the three-qubit phase-flip code.…”
Section: Quantum Error Correction and Quantum Simulations With Molecu...mentioning
confidence: 99%
See 3 more Smart Citations
“…30 On the other, effective qudit QEC codes can be implemented exploiting the d = 2S + 1 levels of a spin S system. 49,51,52 The first approach was investigated in Ref. 30, where it was shown that an [ErCeEr] trimer is a promising molecule to encode a logical qubit protected against dephasing by the three-qubit phase-flip code.…”
Section: Quantum Error Correction and Quantum Simulations With Molecu...mentioning
confidence: 99%
“…Indeed, the performance of the code can be improved by increasing the number of qudit levels, thus making it possible to correct higher-order dephasing errors. This can be done by considering larger nuclear spins, such as 173 Yb in Yb(trensal) 38 (S = 5/2) or 51 V in VOTPP (S = 7/2), 50 shown in Fig. 3-(d,e).…”
Section: Quantum Error Correction and Quantum Simulations With Molecu...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there have been proposals for exploiting their multiple states to specific applications. Relevant examples are the digital quantum simulation of spin-boson models [31], where the qudit encodes boson states, and the implementation of quantum error correction codes [30,32,33]. The latter is particularly promising, as embedding in each basic unit, in this case a molecule, a suitably designed protection against its specific decoherence sources might represent a huge competitive advantage.…”
Section: Introductionmentioning
confidence: 99%